Comparisons of intraocular lens power calculation methods for eyes with previous myopic laser refractive surgery: Bayesian network meta-analysis. Issue 8 (August 2021) - Wei, Ling; Meng, Jiaqi; Qi, Jiao; Lu, Yi; Zhu, Xiangjia
Abstract : For IOL power calculation in eyes with previous myopic laser refractive surgery, the Barrett True-K formula, OCT, and optiwave refractive analysis methods might be more promising. Abstract : Purpose: To compare the accuracy of the methods for calculation of intraocular lens (IOL) power in eyes with previous myopic laser refractive surgery. Setting: EENT Hospital of Fudan University, Shanghai, China. Design: Network meta-analysis. Methods: A literature search of MEDLINE and Cochrane Library from January 2000 to July 2019 was conducted for studies that evaluated methods of calculating IOL power in eyes with previous myopic laser refractive surgery. Outcomes measurements were the percentages of prediction error within ±0.50 diopters (D) and ±1.00 D of the target refraction (% ±0.50 D and % ±1.00 D). Traditional and network meta-analysis were conducted. Results: Nineteen prospective or retrospective clinical studies, including 1217 eyes and 13 calculation methods, were identified. A traditional meta-analysis showed that compared with the widely used Haigis-L method, the Barrett True-K formula, optical coherence tomography (OCT), and Masket methods showed significantly higher % ±0.50 D, whereas no difference was found in the % ±1.00 D. A network meta-analysis revealed that compared with the Haigis-L method, the OCT, Barrett True-K formula, and optiwave refractive analysis (ORA) methods performed better on the % ±0.50 D, whereas the Barrett True-K formula and ORA methods performed better on the % ±1.00 D. Based on the performances of both outcomes, the Barrett True-K formula, OCT, and ORA methods showed highest probability to rank the top 3 among the 13 methods. Conclusions: The Barrett True-K formula, OCT, and ORA methods seemed to offer greater accuracy than others in calculating the IOL power for postrefractive surgery eyes.